ROLE PLAY DALAM PENGAJARAN GRAMMAR UNTUK ANAK PANTI ASUHAN BUKIT HERMON PAPUA BARAT DAYA - Wael, Ahmad; Saputra, Dian; A., Yuliana; Wahid, Bustamin; Musa’ad, Faidah; Saputro, Isnaini Eddy; Ohorella, Hayat Marwan; Hartanti, Rezkiah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This community service aims to analyze the effectiveness of using role play in teaching grammar to children at the Bukit Hermon Orphanage. Grammar and English language learning are important because English is an international language. The effectiveness of grammar teaching can be enhanced through the use of role play as a teaching method. The results of the study show that the role play method is quite effective in improving grammar knowledge. This research was conducted at the Bukit Hermon Orphanage because the students at the orphanage met the criteria needed by the researchers. The data collection method involved conducting pre-tests and post-tests to determine the improvement in knowledge in the samples after receiving treatment. The effectiveness of using role play in teaching grammar was measured through two tests: the pre-test given at the beginning of the session and the post-test given after the treatment or reinforcement by the researchers. The results of the study indicate that the use of role play in teaching grammar is quite effective.